2017
DOI: 10.1021/acs.est.7b01913
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Tolerance: Physiological Consequences of Evolved Resistance to Inhabit a Polluted Environment in Teleost Fish Fundulus heteroclitus

Abstract: Anthropogenic stressors, including pollutants, are key evolutionary drivers. It is hypothesized that rapid evolution to anthropogenic changes may alter fundamental physiological processes (e.g., energy metabolism), compromising an organism’s capacity to respond to additional stressors. The Elizabeth River (ER) Superfund site represents a “natural-experiment” to explore this hypothesis in several subpopulations of Atlantic killifish that have evolved a gradation of resistance to a ubiquitous pollutant—polycycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…Furthermore, certain CYB5 variants in humans result in heritable methemoglobinemia type IV (Hegesh et al, 1986), a condition that causes a buildup of methemoglobin, and a subsequent reduction in oxygen carrying capacity. Similar outcomes of CYB5 gene changes in AW killifish could contribute to the physiological costs of the Elizabeth River adaptations reported in (Jayasundara et al, 2017).…”
Section: Ahr Pathwaysupporting
confidence: 53%
“…Furthermore, certain CYB5 variants in humans result in heritable methemoglobinemia type IV (Hegesh et al, 1986), a condition that causes a buildup of methemoglobin, and a subsequent reduction in oxygen carrying capacity. Similar outcomes of CYB5 gene changes in AW killifish could contribute to the physiological costs of the Elizabeth River adaptations reported in (Jayasundara et al, 2017).…”
Section: Ahr Pathwaysupporting
confidence: 53%
“…As previously described, strong upregulation of genes not associated with the AhR pathway were observed, but it has also been found that the detoxification mechanisms were significantly upregulated in exposed larvae [ 23 , 68 ]. Strong induction of AhR detoxifying systems are not only energetically costly for organisms but also might be responsible for cardiac failure in larvae after oil exposure [ 30 , 69 71 ]. Environmental temperature also influences the level of various xenobiotic metabolizing enzyme activities in fish exposed to crude oil [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, consecutive stressors can, in some cases, have larger impacts on individuals and populations than simultaneous stressors, as in the case of acidified conditions and salinity in crab larvae (Miller et al, 2014) and consecutive warmer air and water temperatures in sea stars (Pincebourde, Sanford, Casas, & Helmuth, 2012), if exposure to the first stressor causes physiological changes that leave an organism vulnerable to a second stressor (e.g., Todgham & Stillman, 2013). Jayasundara et al (2017) showed that killifish adapted to polluted waterways demonstrated altered metabolic and physiological responses to other stressors such as temperature, indicating that adaptation to pollution may compromise the ability of this population to acclimate to other stressors. In addition, each stressor may be inconsistent and may fluctuate over time.…”
Section: Interactions Between Stressorsmentioning
confidence: 99%
“…Jayasundara et al. (2017) showed that killifish adapted to polluted waterways demonstrated altered metabolic and physiological responses to other stressors such as temperature, indicating that adaptation to pollution may compromise the ability of this population to acclimate to other stressors. In addition, each stressor may be inconsistent and may fluctuate over time.…”
Section: Summary Of Urban Impacts Affecting Evolution In Marine Speciesmentioning
confidence: 99%